2008
DOI: 10.1002/ptr.2498
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between chondroprotective and antiinflammatory effects of Withania somnifera root and glucosamine sulphate on human osteoarthritic cartilage in vitro

Abstract: Using a validated explant model of in vitro cartilage damage, the effects of aqueous extracts of Withania somnifera (Ashwagandha) root and glucosamine sulphate (GlcS) were tested on the levels of nitric oxide (NO) and glycosaminoglycans (GAGs) secreted by knee cartilage from chronic osteoarthritis (OA) patients. W. somnifera extracts significantly decreased NO release by explants from one subset of patients (antiinflammatory response) and significantly increased levels of NO and GAGs released by explants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Previous research supports its pharmacological uses, confirming antioxidant, anti-inflammatory (Sumantran et al, 2008), immunomodulatory, anticarcinogenic, antibacterial (Owais et al, 2005), antiparkinsonism (Sankar et al, 2007) and antistress (Geetha and Harish, 2006) properties. Raw plant material and extracts of this species are currently sold as dietary supplements in the USA for increasing energy and endurance, strengthening immune function, and helping the body overcome imbalance.…”
Section: Introductionmentioning
confidence: 87%
“…Previous research supports its pharmacological uses, confirming antioxidant, anti-inflammatory (Sumantran et al, 2008), immunomodulatory, anticarcinogenic, antibacterial (Owais et al, 2005), antiparkinsonism (Sankar et al, 2007) and antistress (Geetha and Harish, 2006) properties. Raw plant material and extracts of this species are currently sold as dietary supplements in the USA for increasing energy and endurance, strengthening immune function, and helping the body overcome imbalance.…”
Section: Introductionmentioning
confidence: 87%
“…Nutritional supplements of many types have been utilized for arthritis, and those containing glucosamine and chondroitin sulfate have been shown to provide pain relief [6]. Other supplements have been tried, but evidence in favor of their use is generally limited to anecdotal experience or in vitro effects [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Elevated NO levels in the ascitic fluid and ROS production by peritoneal macrophages in the PT group were found to be decreased in WS1000 and WS500 groups. Sumantran et al (29) using an explant model of in vitro cartilage damage study on patients with osteoarthritis have also shown marked reduction in NO release when treated with WS root extract.…”
Section: Discussionmentioning
confidence: 97%